The Bugis Culture in Marriage Proposal Communication - Juanda Juanda; Azis Azis (Universitas Airlangga, 2022)
The aim of this study is to investigate the language used in the marriage proposal among the Bugis ethnic group. This research adopts a descriptive qualitative approach. The data was obtained through participant observation and recording techniques of oral dialogues among the Bugis Wajo community in South Sulawesi. The data is presented in the form of a narrative of the proposal process recorded by the authors. Data collection involved recording the speech of the participants, which was then transcribed. The results were analyzed using the Dell Hymes communication ethnographic approach. The findings indicate that the proposal process was conducted formally, with a group of seven men making the proposal. The proposal was accepted and proceeded to the wedding procession with mappasiarekeng, which involves delivering the dowry money and determining the wedding day. The proposal was delivered via delivering the dowry money and determining the wedding day. The proposal was delivered via elong in a serious tone using fixed spoken language that cannot be interrupted, and only spokespersons designated by the proposer, the man and the woman being proposed to, spoke. The speech belongs to the madduta genre.